Recent advances in localized immunotherapy of skin cancers. (21st February 2019) - Russo, Irene; Sernicola, Alvise; Alaibac, Mauro
Skin cancer is the most frequent malignancy in humans. The immune system has long been known to have an important role in defeating cancer. Immunotherapy, which includes various strategies to enhance tumor immunity, currently represents an exciting option for the treatment of skin cancers. Local immunotherapy is a promising therapeutic approach and may improve response rates without inducing systemic toxicity. Here, we review the main localized immunotherapies for the management of skin cancer with a special focus on advanced melanoma, nonmelanoma skin cancer and primary cutaneous lymphoma.